Trends in recreational fisheries and reef fish community structure indicate decline in target species population in an isolated tropical oceanic island. (15th June 2020) - Guabiroba, Helder Coelho; Santos, Maria Eduarda Alves; Pinheiro, Hudson Tercio; Simon, Thiony; Pimentel, Caio Ribeiro; Vilar, Ciro Colodetti; Joyeux, Jean-Christophe
Abstract: Marine recreational fisheries and fish communities have been mostly studied separately, severely hampering the detection of possible interactions. Here we monitored recreational fishery landings (angling and spearfishing) and assessed the reef fish community through underwater visual censuses in Trindade, an isolated oceanic island in the southwestern Atlantic Ocean. The study was conducted in zones of high and low fishing effort, along three different years spread over a seven-year period. We found high catch per unit effort (CPUE; kg*fisher −1 *hour −1 ) associated with high fishing intensity. However, the biomass of the targeted species in the natural environment decreased by 58% over time, while fishing effort increased about 270%, and CPUE decreased by 40%. Inverse relationships between effort and CPUE, and effort and biomass in the environment, were stronger in zones of high fishing effort. We conclude that the recreational fishery activity quickly responded to overfishing, creating a harvesting process that negatively impacted reef fish communities in this isolated oceanic island. Thus, conservation strategies should incorporate long-term recreational catch and fish community monitoring programs. Here we discuss options for the sustainability of the recreational fisheries and reinforce the importance of dialogue among scientists, managers and users for the achievement of conservation goals. Highlights: We analyzed reef fish community and recreational fisheries over a seven years period. Fishing effort increased by 270%, while CPUE decreased by 40%. Biomass of target species in natural environment declined by 58% over the period. Recreational fishery needs management strategies to achieve sustainability.